Empatía y logro de la competencia construye su identidad en estudiantes del quinto ciclo de la institución educativa nivel primaria n° 6010278 El Porvenir, Iquitos 2022 - Chumbe Salas, Wendy Xilene (2023)
The research is based on the following questions: What relationship could exist between empathy and the achievement of the constructs their identity competence in the students of the educational institution? Likewise, what would be the levels of empathy and the achievement of the constructs their identity competence in the students? Therefore, the general objective was: To relate empathy and the achievement of the competence builds their identity in students, and the specific objectives were: To determine the level of empathy and the level of achievement of the competence builds their identity in students. The design of the study considers the field, bivariate and cross-sectional with relational type. The survey and documentary analysis were part of the technique, a questionnaire validated by experts and a registration form were the instruments used to collect information. Fifty-six students in the fifth cycle constituted both the population and the sample. From the results of the inferential analysis, it can be affirmed that fifth cycle students who demonstrate empathy are more likely to develop their identity-shaping skills because rho=0.5,25**; Sig 0.01, allowing us to prove the study hypothesis. High levels of empathy correlate with students' success in acquiring the competence that forms the basis of their individual identity among fifth-cycle students at Escuela Primaria N° 6010278 El Porvenir de Iquitos in the year 2022.